Implementation of The Teaching at The Right Level (TaRL) Approach Through Differentiated Learning of Data Presentation Materials - Ferdianto, Ferry; Susilawati, Tuti (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Student-centered learning should pay attention to the characteristics of students. Differentiated learning is an effort based on the level of needs, learning styles, and characteristics of students. The Teaching at The Right Level (TaRL) approach can be a link to students' learning needs. This research aims to provide an overview of implementing the Teaching at The Right Level (TaRL) approach in differentiated learning in class VII data presentation material at SMP Negeri 16 Cirebon City. This research uses descriptive qualitative methods. The data sources used are the implementation of the learning and field notes obtained during research. Data collection techniques include interviews, observation, and LKPD. The results of this research indicate that the implementation of the Teaching at The Right Level (TaRL) approach through differentiated learning follows the stages of the Teaching at The Right Level (TaRL) approach, namely classifying students' learning needs, preparing differentiated learning plans and their implementation, as well as reflecting and evaluation of learning. The TaRL approach through differentiated learning can effectively increase students' understanding of data presentation material. It is important to implement differentiated learning strategies in creating an inclusive learning environment and supporting the development of each student individually